Prejudice and Health Anxiety about Radiation Exposure from Second-Generation Atomic Bomb Survivors: Results from a Qualitative Interview Study - Kamite, Yuka (Frontiers in Psychology, 2017)
The effect of atomic bomb radiation exposure on the survivors and their children has been a worrisome problem since soon after the 1945 Hiroshima and Nagasaki bombings. Researchers have examined physical and genetic effects; however, no research has focused on second-generation survivors’ (SGS) psychological effects. Consequently, this study shed light on the SGS’ experience of discrimination and prejudice and their anxiety concerning the genetic effects of radiation exposure. This study utilized semi-structured interviews with 14 SGS (10 women, mean age = 56 ± 6.25 years, range = 46–68 years). Data were analyzed using a modified version of the grounded theory approach. Three categories were extracted: low awareness as an SGS, no health anxiety regarding the effect of radiation, and health anxiety regarding the effect of radiation. The results did not reveal that SGS who grew up in the bombed areas experienced discrimination or prejudice. They had little health anxiety from childhood to adolescence. In this study, some of the SGS developed health anxiety about their third-generation children, but only among female participants. Perhaps the transgenerational transmission of anxiety concerning the genetic effects of radiation exposure causes stress, particularly among women with children. However, a change was seen in adulthood health anxiety regarding the effects of radiation, suggesting the possibility that changes in the psychological experiences of SGS can be observed throughout their lifetimes and that their own health status, and that of their children, the third-generation survivors, affects their health anxiety regarding radiation.